Prevalence of anemia in type II diabetes mellitus patients - Reddy, Sreenivas; Reddy, Molugu Divya (International Journal of Research in Medical Sciences, 2019)
Background: Anemia is a common haematological finding in diabetic patients. The prevalence of anemia in the patients with diabetes is two or three times higher than in patients with comparable renal impairment and iron stores in the general population. As India is foreseen a diabetic capital of the world, it becomes imperative to recognize co-morbidities such as anemia at the earliest. The aim of this study was to determine the prevalence of anemia among patients with type 2 diabetes. Author conducted a prospective analysis of 100 diabetic patients visiting the outpatient clinic in our institution. Duration of study is One Year (November 2016 - December 2017). Study perform at Om Sai Hospitals, Balapur, Hyderabad, Telangana, India. A 100 patients suffering from type 2 Diabetes Mellitus, attending Outpatient Department of General Medicine, were included in the study. Methods: All the patients were subjected to detailed history, through clinical examination and investigation. Patients’ blood samples were analyzed for Glycated hemoglobin (HbA1C) values and hemoglobin (Hb) levels. The prevalence of anemia was then determined defining anemia by an Hb level <13.0 g/dL for men and <12.0 g/dL for women. Results: The prevalence of anemia in this study population was found to be 43%. The prevalence of anemia is significantly greater in diabetic females than in diabetic males and in poorly controlled diabetics than those with glycemic status under control. Conclusions: We conclude that anemia is a prevalent finding in patients with type 2 diabetes mellitus and represents significant unrecognised burden.